Influence of ultrasonic treatment on the structure of high-carbon steel - K. Nowacki (Metalurgija, 2011)
Discussion on the results of industrial tests of sound amplification of high-carbon steel in a 130 kg ingot mould. The sound amplification was conducted using a waveguide immersed in liquid steel and connected with a piezoelectric head excited acoustically with a power oscillator. The ultrasonic treatment had several purposes, one of which was inducing motion in the liquid steel during solidification. As result of the tests conducted, it was determined that, in ingots submitted to ultrasonic treatment compared with the ingots solidifying without, the axial segregation of elements was reduced and the share of the equiaxed zone in the area of acoustic wave impact increased by several percent.